L’alimentation durable en France : enjeux de politisation et de communication - Clémentine Hugol-Gential (Communiquer)
This contribution focuses on the sustainable dimensions of food policies and discourses in France. The rise of sustainable food in recent years and its media coverage have caused a paradigmatic shift from healthy to good to eat, leading to changes in public policies and social representations. This research is carried out within the framework of the implementation of a territorial policy of a medium-sized French metropolis around sustainable food. Several methodologies are deployed (discourses analysis, semi-structured interviews, focus-groups, online survey) here to, first of all, capture the discourses circulating in the public and media space concerning sustainable food. In a second step, it is a question of understanding the practices, the social representations and of implementing a participative device allowing a reconfiguration of public policies at the local level for food democracy. The work as a whole highlights the political and communication dimensions of sustainable food.